The impacts of US Fed interest rate liftoff on Southwest Asia stock markets, sovereign bond and currencies - Ooi, Teik Khim (2017)
In 2015, Federal Funds Futures (FFF) that represented market expectation on Federal Funds Rate (FFR) in future indicated market expected more gradual interest rate lift-off in future, which should boost the ASEAN financial market, yet it suffered a relatively big decline possibly due to surge in global risk as reflected in Volatility Index (VI X). This paper aims to examine the impact of US interest rate lift-off on the performance of ASEAN equities, currencies and sovereign bond during that period. The examination period ranged from FOMC meeting in 29-30 October 2014 when they ended the asset purchase program until 19 Feb 2016 when relevant data was collected for econometric analysis (hereafter 2015 ASEAN slump). Based on the capital push-pull factors framework, two models are developed to test the impact of US interest rate lift-off. First model use FFF as a proxy for market expectation on interest rate lift-off. While, the second model traces the announcement effect of Non-Farm Payroll (NFP) figure. Amid forward guidance, both FFF and NFP are good proxies for market expectation for interest rate lift-off. The regression results of both models conclude that i) interest rate lift-off affects A SEAN stock markets and sovereign bond, but it is inconclusive for ASEAN currencies. ii) VIX affects ASEAN stock markets and currencies, but it is inconclusive for ASEAN sovereign bond. Subsequently, an extension regression is done to confirm that VIX and FFF is negatively correlated. Based on the more reliable model I (using FFF), it implies the negative effect of spike in VIX dominated the positive effect from lower market expectation on interest rate lift-off, which led to decline in ASEAN financial market during 2015 A SEAN slump.